The Characteristic of RLD-Governor and its fault finding - HUANG De-ming; SONG Zhong-yan (浙江大学学报. 农业与生命科学版, 2001)
The RLD-governor is a kind of advanced governor. Its characteristic is to supply the engine with fuel, in the correct ratio, over a wide range of engine speeds and loads. It can coordinate all kinds of engine which used in auto. Since its complicated constructure, people would feel it difficult to use, repair and adjust RLD-governor. This paper analyses RLD-governor's fundamental principle, special features and some faults which can be fixed.